PELATIHAN BAHASA JEPANG DASAR UNTUK MAHASISWA POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN BENGKULU - Raden Novitasari; Kuraesin, Uning; Ariestafuri, Nurza; Rahardjo, Hardianto; Tresnasari, Ningrum (LPPM Universitas Bina Bangsa, 2024)
The impact of low birth and death rates in Japan has resulted in an increase in the number of elderly Japanese people. And gradually Japan has become short of productive and professional workers in various fields. As a result of this condition. The Japanese government has begun to open up quite wide opportunities for other countries for foreign workers to enter and work in Japan. One way the Japanese government has done this is by opening cooperation with other countries, for example with Indonesia. The Indonesia-Japan cooperation is packaged with the IJ-EPA (Indonesia-Japan Economic Partnership Agreement) cooperation scheme which includes cooperation in the provision of nursing workers.The implementation of this cooperation is in the form of a program for procuring nursing workers to be employed as nursing workers in Japan. Along with the progress of this program, the government has experienced various obstacles, starting from the requirements to become a nurse in Japan, and the main factor is the obstacle of mastery of the Japanese language and cultural knowledge. Meanwhile, the workers who are sent to Japan to become nursing workers do not have a good command of the Japanese language and culture.Therefore, the Community Service Team of the Japanese Language Study Program, Widyatama University, feels that in order to avoid miscommunication, mastery of the Japanese language and culture is considered quite important. With sufficient language proficiency, it is expected to reduce existing obstacles. The Community Service Team will provide training in the form of introducing Japanese nursing terms in Japanese. This community service activity will be carried out in the 3rd week of December 2022 at POLTEKKES Bengkulu City, Jl. Indragiri Padang Harapan No. 3 Padang Harapan, Gading Cempaka District, Bengkulu City. The material that will be delivered to students is Basic Japanese Language training.